1995
DOI: 10.1111/j.1574-6968.1995.tb07727.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of individual cytoplasmic pH values in a population of the yeastSaccharomyces cerevisiae

Abstract: Fluorescence ratio imaging microscopy using pH-sensitive fluorescent dyes makes it possible to evaluate statistical distribution of intracellular pH in a population of the yeast S. cerevisiae examined in a thin layer of suspension in a Petri dish. The distribution appears to fit a Gaussian curve with a half-width around the 0.4 pH unit. The curve became slightly narrower after resuspension in a strong buffer; the mean values shifted with the pH of the buffer. The shape of the distribution curves of both restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Because marked fluctuations of the pH often occur in biological systems, pH homeostasis has to compensate for changes in the environment. The intracellular pH value of yeast is kept at a value of between pH 5 and 6 (32). Optimum pH for activity of yeast chorismate mutase between 5.0 and 6.5 coincides with the findings for intracellular pH values and the cellular biochemistry here seems to be well adapted to intracellular conditions.…”
Section: Discussionsupporting
confidence: 80%
“…Because marked fluctuations of the pH often occur in biological systems, pH homeostasis has to compensate for changes in the environment. The intracellular pH value of yeast is kept at a value of between pH 5 and 6 (32). Optimum pH for activity of yeast chorismate mutase between 5.0 and 6.5 coincides with the findings for intracellular pH values and the cellular biochemistry here seems to be well adapted to intracellular conditions.…”
Section: Discussionsupporting
confidence: 80%
“…This pH requirement for RhAG-mediated complementation correlates with the predicted plasma membrane proton gradient (Table I). The intracellular pH (pH i ) in yeast is correlated with the pH of the medium (pH o ) (19). At acidic pH o 4.3-5.3, the pH i is relatively alkaline , so the direction of the proton gradient is inward.…”
Section: Discussionmentioning
confidence: 99%
“…Early 31 P NMR studies indicated that yeast intracellular pH was not affected by the external pH conditions or the presence of NH 4 ϩ (41). However, several subsequent studies found that the intracellular pH of yeast followed the external pH when the extracellular medium was either strongly buffered (18,(42)(43)(44) or contained weak organic acids such as acetate, butyrate, or succinate (19,(45)(46)(47). This suggests that the plasma membrane of yeast is permeable not only to NH 4 ϩ but also to other weak acids.…”
Section: Nh 4 ϩ -Mediated Acidification Of the Yeast Vacuolementioning
confidence: 99%